Perlindungan Hukum Bagi Pengungsi Rohingya Terhadap Hak Atas Suaka di Indonesia - Mutthu, Zamirah Zahra; Afifah, Wiwik (Media Hukum Indonesia (MHI), 2025)
The conflict involving the Rohingya ethnic group in Myanmar is a longstanding and complex issue, rooted in discrimination against their citizenship status and prolonged interethnic tensions. The enforcement of Myanmar’s 1982 Citizenship Law has led to the Rohingya losing official recognition as citizens, along with their fundamental rights. The Myanmar government regards them as illegal immigrants from Bangladesh, despite historical evidence indicating that the Rohingya have resided in the Arakan (now Rakhine) region long before the country's independence. This discrimination has been further exacerbated by the Burmanization policy implemented by the military regime, which restricts the Rohingya's rights in various aspects of life, such as education, employment, freedom of movement, land ownership, and family planning. The escalation of conflict in 2012 triggered a mass exodus to several countries, including Indonesia. Although Indonesia is not a party to the 1951 Refugee Convention, the country has shown humanitarian concern by providing temporary shelter for Rohingya refugees. Nevertheless, this reception has not always proceeded smoothly due to resistance from local communities, particularly in Aceh, influenced by past experiences and the spread of misinformation. This issue underscores the importance of international cooperation and a deeper understanding of refugee protection principles in order to uphold humanitarian values and maintain regional stability.